Cosmic ray intensity for about five solar cycles. (July 2015) - Storini, M; Signoretti, F; Re, F; Diego, P; Marcucci, M F; Laurenza, M; Massetti, S.; Parisi, M
Abstract: Continuous records of the cosmic ray nucleonic component have been achieved at Rome (SVIRCO Group) by using data from different types and locations of neutron monitors (first at La Sapienza University: 41.90°N, 12.52°E, altitude about 60 m a.s.l., and then at Roma Tre University: 41.86°N, 12.47°E, about sea level). The normalized data, covering the whole period from July 1957 to June 2014, are available to the scientific community by simple request. Here we illustrate some useful results derived from them.